PROS AND CONS OF THE DEATH CRIME IN INDONESIA - Muhammad Akbar; Abdullah Abdullah (Fakultas Hukum Universitas Muhammadiyah Palu, 2021)
This paper deals with capital punishment imposed on certain crimes. This punishment is governed in the Indonesian Penal Code and other regulations which haver been still in use in Indonesian. Of these regulations is Code No. 26/2000 on Human Rights Court. If Indonesia still imposes death punishment to those commiting certain crimes, it should amend Article 28/A in order that it does not contradict with the Basic Coder of 1945.